Perancangan Interior Makeup & Beauty Community Center Di Surabaya - Kim, Renata; Sari, Sriti Mayang (Intra, 2019)
The growth of the cosmetics industry in Indonesia nowdays was caused by the increasing lifestyle and public awareness, especially womens, that pays attention to their appearance and beautify themselves. Moreover, social media such as Facebook, Instagram and others are also some factors in this phenomenon. This issue brings up a new type of public figure who has the knowledge and skills in the beauty fields, both formal and self-taught educational backgrounds, known as the beauty vlogger. Surabaya Glam Squad (SbyGlamSquad) is a beauty vlogger community, and one of the beauty activist in Surabaya. Periodically, they often hold make-up or beauty class events and gatherings with fellow make-up lovers to build a sense of family and share the latest tips and information in the beauty industry, even though there is no special space for these activities. "The Beauty Playground" as the concept is a design solution that aims to create space designs that shows the characters of this community, supported with fun and aesthetic atmospheres from the details on the walls to the lightings, and to be able to accommodate the community activities. Especially, to increase the existance of the community not only through the social medias, exclusive community members and make-up lovers only, but also on the general public.